The effect on absence of clinical history and demographic data of genitourinary cases in discovering agreement between inter- and intra-observers / Siti Norbaya Mohamad ... [et al.] - Mohamad, Siti Norbaya; Abu, Mohd Nazri; Ahmad, Mardhiah; Roslan, Nur Amirah; Daklan, Nur Hidayah; Roslan, Najwa Nadeera; Abd Malek, Nur Nadirah; Alihad, Nur Adlina; Md. Isa, Khairil Anuar (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
In this genitourinary cytology study, glass slides were provided to the observers without demographic data and clinical history during cases review. The aim of this study is to evaluate inter- and intra- observer reliability in genitourinary cases without support of clinical history and demographic data information. Five slide observers were selected among students to screen 26 genitourinary cases using light microscope. Average of Fleiss Kappa and Cohen Kappa for inter- and intra-observer agreement was in between 0.1 to 0.5 indicating ‘fair agreement’. The results concluded that Medical Laboratory Technology UiTM students have abilities in recognizing the genitourinary cytology slides based on morphological characteristics even without the support of demographic data information and history.